MODELLING AUTOMATIC EXPOSURE CONTROL RESPONSE TO THE PRESENCE OF THE PATIENT SCANNING BED IN A HYBRID PET/CT SCANNER. Issue 3 (11th October 2021) - Cournane, Seán; Reade, Matthew; McCavana, Jackie; Lucey, Julie
Abstract: Automatic Exposure Control (AEC) systems optimise radiation dose to the patient while providing adequate image quality. This study examined the effect that the increased localiser region of interest of a hybrid PET/CT has on the CTDIvol, focussing on the role of extraneous objects and patient attenuation profiles. A Siemens Biograph™ 16 Horizon PET/CT system and a Siemens Somatom Sensation 64, both employing the Siemens CAREDose 4D AEC system, were used for acquisition of a range of phantoms. The effect of patient miscentring and effect of the patient bed impinging on the localiser was established and modelled. For PA localiser scans, a non-linear relationship between miscentring and CTDIvol was observed, attributable to the presence of the patient bed being misinterpreted as the patient width. The model identified how the presence of the patient bed led to an increase in the CTDIvol significantly larger than expected ( 12%, or 1 mSv), particularly prevalent for smaller patients.